Linking Digital Retail Strategies to Economic Performance: The Effect of Omnichannel Strategy, E-Service Quality, and Customer Experience on Customer Retention at Sociolla Skincare - Fertansyah, Ammalya Ananda; Waluyo, Minto (Yayasan Riset dan Pengembangan Intelektual, 2025)
This research endeavors to investigate the influence of an omnichannel strategy, customer experience, and e-service quality on customer satisfaction and repurchase intention within the framework of Sociolla e-commerce. The background of this study is driven by the increasing competition in beauty e-commerce and the need for companies to build a consistent consumer experience across channels. Data were gathered through a survey administered to 100 respondents who actively utilized Sociolla within the past six months. The analytical methodology uses the AMOS framework, utilizing Structural Equation Modeling (SEM). The results of the study reveal that the omnichannel strategy, customer experience, and e-service quality have a substantial impact on customer satisfaction. However, it is important to note that these factors do not significantly affect repurchase intention. Additionally, customer satisfaction itself exhibits a notable influence on repurchase behavior. The implications of this study show the importance of seamless multi-channel integration and digital service quality in creating a satisfying experience and driving customer loyalty.